2011
DOI: 10.1111/j.1398-9995.2011.02549.x
|View full text |Cite
|
Sign up to set email alerts
|

PARP-1 deficiency blocks IL-5 expression through calpain-dependent degradation of STAT-6 in a murine asthma model

Abstract: Background We recently showed that PARP-1 may play a role in allergen (ovalbumin)-induced airway eosinophilia, potentially through a specific effect on IL-5 production. We also reported that while IL-5 replenishment promotes reversal of eosinophilia in lungs of PARP-1−/− mice, IL-4 or IgE replenishment do not, suggesting a potentially significant regulatory relationship between PARP-1 and IL-5. Objective To explore the mechanism by which PARP-1 regulates IL-5 production and to determine how PARP-1 inhibition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
53
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 31 publications
8
53
0
Order By: Relevance
“…In our study, we found that LPS induced significant neutrophil infiltration in lungs which is in agreement with earlier reports [61][62][63]. Previously, we have shown that PARP inhibition blocks the lung inflammation in the context of ALI and asthma [29,31,32,[64][65][66][67]. Pharmacological inhibition of PARP has been investigated in various experimental conditions of ALI or other organ(s) injury mediated by systemic exposure of LPS [31,32,[67][68][69][70].…”
Section: Discussionsupporting
confidence: 94%
“…In our study, we found that LPS induced significant neutrophil infiltration in lungs which is in agreement with earlier reports [61][62][63]. Previously, we have shown that PARP inhibition blocks the lung inflammation in the context of ALI and asthma [29,31,32,[64][65][66][67]. Pharmacological inhibition of PARP has been investigated in various experimental conditions of ALI or other organ(s) injury mediated by systemic exposure of LPS [31,32,[67][68][69][70].…”
Section: Discussionsupporting
confidence: 94%
“…It is believed that this enzyme mediates inflammation through promotion of cell death by means of ATP depletion as well as transcription of inflammatory factors (Datta et al, 2011). Upon activation, PARP-1 catalyzes the formation of poly (ADP-ribose) chains by transferring (ADP-ribose) from NAD onto itself and nuclear acceptor proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the NFjB co-activator function of PARP-1 has been made responsible for the effects of PARP inhibitors in Th1 diseases (and this may also contribute to the pathology of Th2-mediated conditions), recently a novel mechanism has been described for asthma, a prototypical Th2-mediated disease. Datta et al [64] have demonstrated in a murine model of asthma that inhibition of eosinophil migration in PARP-1 À/À mice is controlled at a step downstream of IL-4 and upstream of IL-5. PARP-1 was found to stabilize STAT-6 protein (without affecting mRNA) in an allergen-stimulation dependent manner.…”
Section: Inflammatory Diseases Mediated By Poly(adp-ribose) Polymerasesmentioning
confidence: 99%